Granulomatous Lymphadenitis in a Dog Caused by Mycobacterium intracellulare - Souza, Cristiane Trevisan Viana de; Prass, Daniela Souza; Souza, Roberto Lopes; Furlan, Fernando Henrique; Colodel, Edson Moleta; de Sousa, Alessandra Tammy Hayakawa Ito; Dutra, Valeria; Sousa, Valeria Regia Franco (Acta Scientiae Veterinariae, 2022)
Background: Mycobacteriosis is caused by bacteria belonging to the genus Mycobacterium, with considerable zoonotic potential and risk to public health. Infection in dogs is rare and is usually associated with immunosuppression, resulting from eating meat or contact with contaminated soil or fomites. Dogs are also known as potential sources for the spread of atypical tuberculosis in humans and other animals. This paper aims to describe the clinical, cytological, histopathological, and molecular findings of a male canine seen at University Veterinary Hospital of Cuiabá, Mato Grosso, with generalized lymphadenomegaly associated Mycobacterium intracellulare infection. Case: A 2-year-old male Lhasa Apso dog was referred to the University Veterinary Hospital in Cuiabá city, located in the Midwest region of Brazil. The patient had a history of intermittent claudication of the left pelvic limb for approximately 6 months and lymphadenomegaly with progression for approximately 2 months. The dog had wheezing and generalized lymphadenopathy (submandibular, axillary, and popliteal lymph nodes); cryptorchidism was also observed. A complete blood count revealed nonspecific results, and in the serum biochemical profile, the values of urea, creatinine, albumin, and alanine aminotransferase were within the reference range. No changes were observed on the radiography of the femurotibiopatellar joints. Considering the generalised lymphadenopathy, fine needle aspiration cytology and histopathological examination through biopsy of the lymph nodes was performed. On the cytology and histopathology, numerous negative images of moderately refringent bacillary structures distending the cytoplasm from the macrophages was found. The samples were also subjected to special Ziehl-Neelsen staining, which confirmed an accentuated and diffuse granulomatous lymphadenitis associated with alcohol acid-resistant bacilli. The polymerase chain reaction (PCR) was used to amplify the DNA of the lymph node fragment for the hsp65 gene, which was subjected to genetic sequencing and construction of a phylogenetic tree, with 99.77% genetic similarity for the species M. intracellulare. As treatment, doxycycline (10 mg/kg twice a day for 60 days) and enrofloxacin (5 mg/kg once a day for 10 days) were prescribed. However, the canine suffered car trauma leading to a fractured pelvis, which motivated the owner to opt for euthanasia at another veterinary establishment. Discussion: In the reported case, it was not possible to determine the source of infection, as the owners reported that the animal lived inside the house with only sporadic access to the street. The clinical signs manifested by this dog were nonspecific, and only the signs of generalised lymphadenopathy could be correlated with the signs expected in the infection with this mycobacterium. The hematological and biochemical laboratory findings were nonspecific, and it did not demonstrate the involvement of other organs. Considering the findings in cytology and histology, mycobacterial infection can be suspected. The diagnosis was confirmed through pathological and molecular findings. In this case, the PCR technique was used with partial amplification of the hsp65 gene and subsequent genetic sequencing, making it possible to identify a species like M. intracellulare (99.77% similarity). Due to euthanasia for another reason, it was impossible to monitor the dog’s treatment and investigate other changes in the post mortem examination, especially the pulmonary lesions frequently described in M. intracellulare infection in humans. Keywords: Mycobacterium avium complex (MAC), canine, infection, non-tuberculous mycobacteriosis.